Factors that account for inter-individual variability of lateralization performance revealed by correlations of performance among multiple psychoacoustical tasks - Ochi, Atsushi; Yamasoba, Tatsuya; Furukawa, Shigeto (Frontiers in Neuroscience, 2014)
This study explored the source of inter-listener variability in the performance of lateralization tasks based on interaural time or level differences (ITDs or ILDs) by examining correlation of performance between pairs of multiple psychoacoustical tasks. The ITD, ILD, Time, and Level tasks were intended to measure sensitivities to ITD; ILD; temporal fine structure or envelope of the stimulus encoded by the neural phase locking; and stimulus level, respectively. Stimuli in low- and high-frequency regions were tested. The low-frequency stimulus was a harmonic complex (F0 = 100 Hz) that was spectrally shaped for the frequency region around the 11th harmonic. The high frequency stimulus was a ‘transposed stimulus’, which was a 4-kHz tone amplitude-modulated with a half-wave rectified 125-Hz sinusoid. The task procedures were essentially the same between the low- and high-frequency stimuli. Generally, the thresholds for pairs of ITD and ILD tasks, across cues or frequencies, exhibited significant positive correlations, suggesting a common mechanism across cues and frequencies underlying the lateralization tasks. For the high frequency stimulus, there was a significant positive correlation of performance between the ITD and Time tasks. A significant positive correlation was found also in the pair of ILD and Level tasks for the low- frequency stimulus. These results indicate that the inter-listener variability of ITD and ILD sensitivities could be accounted for partially by the variability of monaural efficiency of neural phase locking and intensity coding, respectively, depending of frequency.